Physical Accessibility and Employment among Older Adults in California. Issue 12 (December 2019) - Blumenberg, Evelyn; Schouten, Andrew; Pinski, Miriam; Wachs, Martin
Older adults are delaying retirement and remaining in the paid workforce longer than in previous decades. There are many potential explanations for this trend. In this study, it is hypothesized that the ease or difficulty of traveling may significantly influence the labor force participation of older adults, just as it does for other working-age adults. As they age, older adults can face a number of barriers to mobility. The hypothesis is tested using data from the 2012 California Household Travel Survey (CHTS) and propensity score matching. The paper focuses on the effects of automobile ownership and transit access on the employment status of older adults (60+), controlling for a host of characteristics associated with the likelihood of employment. The analysis shows that transportation access has a substantial and positive association with employment for older adults, particularly older adults living in low-income households (those earning less than 35, 000 per year). Access to jobs by public transit is especially influential among low-income older adults who live in households without automobiles. The findings underscore the importance of enhancing the transportation environment such that it allows older adults to travel regularly on their own by car or, in dense urban neighborhoods, by public transit. Limitations to this study suggest the need for additional quantitative analysis of longitudinal data as well as qualitative analysis of data from interviews and focus groups.